A preliminary assessment of physical work exposures among electronic waste workers at Agbogbloshie, Accra Ghana - Acquah, A.A.; D’Souza, C.; Martin, B.J.; Arko-Mensah, J.; Botwe, P.K.; Tettey, P.; Dwomoh, D.; Nti, A,A.; Kwarteng, L.; Takyi, S.; Quakyi, I.A.; Robins, T.G.; et al. (International Journal of Industrial Ergonomics, 2021)
Occupational exposure associated with unstructured, informal e-waste recycling has received very limited attention. This study aimed to quantify the occupational physical exposures among informal e-waste workers at the largest e-waste site in Africa. A cross-sectional field survey of 163 male e-waste workers was conducted using a self-report occupational physical activity questionnaire, along with direct work observations, and pedometer estimates of walking activity for a subset of workers (n = 42). Results indicated significant differences in self-reported 7-day work exposures among the three main e-waste job categories, namely, collectors (n = 70), dismantlers (n = 73) and burners (n = 20). Prolonged walking, sitting and standing on five or more days in the workweek was frequently reported by collectors (87%), dismantlers (82%) and burners (60%), respectively. Nearly 90% of collectors and burners and 60% of dismantlers reported lifting and carrying on five or more days in the workweek. The exposure combinations identified suggest a risk for musculoskeletal disorders (MSDs). Findings call attention to the need for research examining potential associations between physical exposures and MSDs affecting e-waste workers in Agbogbloshie. The high exposure variability both between and within workers has implications for future exposure assessments conducted in unregulated, informal work settings.
Research Article
Keywords: E-waste; Informal recycling; e-waste collection; Physical activity exposure; OPAQ; Agbogbloshie